Acoustic Characterization of Patterning Degradation during Wet Etching. (11th September 2015) - Virgilio, Christophe; Garnier, Philippe; Foucaud, Mathieu; Devos, Arnaud; Pinceau, David; Carlier, Julien; Campistron, Pierre; Nongaillard, Bertrand; Neyens, Marc; Broussous, Lucile
Abstract : Photoresist degradation can occur during wet etching processes due to chemicals diffusion through the polymer. The adhesion of the resist is not guaranteed anymore and damage on the resist / material interface appears. This phenomenon is usually monitored by optical methods. However, invisible resist degradation cannot be detected and the physical nature of the resist / material modification remains unknown. A high-frequency acoustic echography method has been developed to overcome these problems and has been performed to study the apparition of blisters in a deep UV photoresist exposed to a Standard Clean 1 solution. This technique allows the quantitative detection of resist degradation even if blisters cannot be seen in the resist. It has also been found that gas pockets appear during blisters formation.